Workforce issues in the Australian National Disability Insurance Scheme: Complex support needs ready?. Issue 1 (2nd January 2016) - Dowse, Leanne; Wiese, Michele; Smith, Louisa
ABSTRACT: Australia's implementation of the National Disability Insurance Scheme (NDIS) relies heavily on a skilled workforce, competent to meet the needs of scheme participants. This article raises concerns about NDIS workforce planning issues as they relate to people with intellectual disabilities and complex support needs. The article uses population level measures to estimate the likely significant presence of NDIS participants with intellectual disabilities and complex support needs, and summarises the predicted growth in the disability workforce. Using these data together with the research literature, a number of challenges to developing and maintaining the skills of the workforce are proposed. If the NDIS is to ensure a workforce ready to support participants with intellectual disabilities and complex support needs, these challenges require immediate action, the absence of which could mean the very real potential of market failure for this vulnerable group.